The r-process in black hole-neutron star mergers based on a fully general-relativistic simulation. Issue 1 (January 2016) - Nishimura, N; Wanajo, S; Sekiguchi, Y; Kiuchi, K; Kyutoku, K; Shibata, M
Abstract: We investigate the black hole-neutron star binary merger in the contest of the r-process nucleosynthesis. Employing a hydrodynamical model simulated in the framework of full general relativity, we perform nuclear reaction network calculations. The extremely neutron-rich matter with the total mass 0.01 M ⊙ is ejected, in which a strong r-process with fission cycling proceeds due to the high neutron number density. We discuss relevant astrophysical issues such as the origin of r-process elements as well as the r-process powered electromagnetic transients.